Aboveground biomass estimation of tropical street trees. Issue 1 (4th January 2018) - Ngo, Kang Min; Lum, Shawn
Abstract: Urban trees provide numerous ecosystem services to city residents, including carbon storage and sequestration. Quantifying carbon sequestered in urban trees provides estimates of carbon emissions offset. Estimation of urban tree aboveground biomass (AGB) has traditionally been based on the use of allometric equations developed for forest trees. However, urban and forest trees often have different architecture, so forest equations may not provide accurate estimates. We destructively sampled 31 street trees in Singapore and compared their DBH (diameter at breast-height)-AGB relationship to six tropical forest allometric equations. We found that equations developed for tropical forests overestimated street tree AGB by 33–57% and 35–324% for trees with 30 and 60 cm DBH, respectively. Equations for secondary forests underestimated street tree AGB but had closer estimates, ranging from −34 to − 12% and −212 to − 39% for trees 30 and 60 cm DBH respectively. Models for temperate urban trees underestimated tropical tree AGB for trees >15.9 cm DBH, with errors ranging from 34 to 43%. These discrepancies in estimates obtained from tropical forest and temperate urban tree equations are very likely due to differences in tree architecture, mainly caused by differing growth environment and climate. Given that Singapore is now implementing a complete country-level carbon accounting programme, estimates obtained from the allometric equation developed in this study will provide improved estimates for street tree biomass.